Effect of 'chlorine‐free' cleaning of milking equipment on the microbiological quality and chlorine‐related residues in bulk tank milk. (3rd March 2022) - Gleeson, David; Paludetti, Lizandra; O'Brien, Bernadette; Beresford, Tom
Abstract : The influence of new chlorine‐free milking equipment cleaning protocols was compared with that of traditional chlorine‐based protocols from the perspective of the microbiological quality and chlorine‐related residues in bovine bulk tank milk. Commercial dairy farms using different cleaning protocols were identified, and bulk tank milk from these farms was sampled and tested on three occasions during the milk production season for microbial load and the chlorine‐related residues trichloromethane and chlorate. Total bacterial counts and residue levels were lower with chlorine‐free than with chlorine‐based protocols,  demonstrating the new chlorine‐free cleaning protocols had a positive impact on milk quality when implemented on commercial farms. Abstract : Impact of milking equipment cleaning protocols on raw milk quality.